Effects of Non-verbal Priming on Attachment-Style Activation - Sim, Suhyung; Shin, Ji-eun; Sohn, Young Woo (Frontiers in Psychology, 2019)
Using an affective priming procedure, two experiments examined the effects of nonverbal cues on activating attachment styles. In Study 1, the secure attachment group, which was primed nonverbally, showed higher levels of self-esteem, interpersonal competence, and positive affect than the insecure attachment group, which was also primed nonverbally. In contrast, no significant difference was found between the two attachment groups that were primed verbally. In Study 2, using a different priming method and adding a neutral group, similar interactions between priming modality (nonverbal or verbal cues) and attachment styles were found: The differences in self-esteem, interpersonal competence, and positive affect between the secure attachment group, neutral group, and insecure attachment group were greater when primed nonverbally than when primed verbally. Finally, the limitations of the research and recommendations for follow-up study are discussed.